A Novel Protocol for the Regioselective Bromination of Primary Alcohols in Unprotected Carbohydrates or Glycosides - 薛伟华 张立芬 (Chinese journal of chemistry, 2012)
The regioselective and efficient bromination of primary hydroxyl groups in unprotected carbohydrates or glycosides is successfully achieved by using （chloro-phenylthio-methylene）dimethylammoniumchloride （CPMA） in the presence of tetrabutylammonium bromide （TBAB） in dry DMF.